Chapter Il gioco delle mafie. Regolazione, mercati e criminalità nell’azzardo - Esposito, Federico; Picarella, Lorenzo; Sciarrone, Rocco (Firenze University Press, 2025)
This paper investigates the relationship between Italian mafias and gambling in the light of the sector’s rapid growth over the last thirty years. In the Nineties, the Italian government decided to legalize and then liberalize gambling. This decision has been justified on the ground of both economic and public order reasons. At the time, Italy was facing economic crisis and the gambling sector could generate an important financial income for the state through taxation. Moreover, the government claimed that legalizing gambling would have counter the long-standing influence of organized crime in the sector. From this perspective, legal gambling is seen as the only way to curb illegal gambling. However, this view is largely contradicted by the empirical evidence, which shows that the mafias have gradually migrated from illegal gambling to legal, government-controlled gambling. By reviewing a number of judicial sources, the paper investigates the presence of mafia-type groups in the legal gambling sector, focusing on slot machines’ and online gambling’s supply-chain which have been found to be the most infiltrated ones. We conclude that the problem of criminal influence should be approached not as a question of legal versus illegal gambling, but by addressing the regulatory model currently implemented in Italy.